Evaluation of kikuyu grass wetland for wastewater treatment efficiency from malt factory, Ethiopia - Dessie Tibebe; G/ Hiwot Ambelu; Yezbie Kassa (BMC, 2024)
Abstract Background The majority of existing industries in Ethiopia discharge untreated effluents into nearby water bodies, streams and open land. The wastewater generated by Gondar malt factory (GMF) was disposed freely and join a natural wetland implemented for the treatment of the wastewater. The objective of the study was to analyze and characterize wastewater from GMF and to evaluate the effectiveness of the wetland for the treatment purpose. Methods Different Physicochemical quality indicators (color, turbidity pH, temperature, Total Dissolved solids, Total Suspended solids, total solid, conductivity, alkalinity, hardness, nitrate, phosphate, sulfate, free chlorides, heavy metals-(Cd, Cr, Fe, Mn, and Pb)and Biological Oxygen Demand were measured according to the standard procedures. Data was analyzed using Statistical Package for Social Sciences (SPSS-25). Analysis of Variance (ANOVA) was used to find whether significant differences existed in the different sampling stations for the parameters studied. P value less than 0.05 was considered to show significant difference. Results The results of this study revealed that most of the quality indicators were improved in value after the water passed through the wetland except for alkalinity M, sulfite, Mn, temperature and pH. From ANOVA result, it was noted that there was a significant mean difference between the stations except for chromium, manganese and lead. The result showed that the wetland plays a great role in the removal of pollutants where the best performance was obtained at removal efficiency of 96.188% PO4 HR ,75.63% Nitrate,>99% Cl2, ammonia and nitrite 99.99%, 92.77% sulfate,84.36% Total hardness,87.43% color, and for others it is ranged between 30 and 60%. Conclusion the study concluded that GMF wetland was almost effective and had potential in treatment of the wastewater from the discharging facilities (especially for nutrients, alkalinity P, hardness, color and chloride). It is recommended that wetlands should be conserved and used as wastewater treatment facility.